The complete guide to decks : how to plan & build your dream deck : with complete deck plans. (Complete guide, 2011)
"Featuring the most-current and popular deck-building materials being used today, this book uses full-color, step-by-step photography to show homeowners how to build, maintain and customize a deck"--Provided by publisher.